2007
DOI: 10.1186/1751-0759-1-20
|View full text |Cite
|
Sign up to set email alerts
|

Insecure attachment is associated with the α-EEG anomaly during sleep

Abstract: BackgroundThe α-EEG anomaly during sleep, originally associated with chronic pain, is noted in several psychiatric and medical conditions and is also present in some normal subjects. The exact significance of the α-EEG anomaly is uncertain, but it has been suggested to be a nonspecific response to a variety of noxious stimuli. We propose that attachment insecurity, which is often associated with a state of hypervigilance during wakefulness, may be associated with the α-EEG anomaly during sleep.MethodsThirty on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Troxel et al (2007) reported that, among depressed women, those with higher levels of attachment anxiety had a lower percentage of stage 3/4 sleep and shorter sleep latencies. In anxiously attached individuals, Sloan et al (2007) reported an association between insecure attachment and the degree of α-power sleep (a form of light sleep), independent of anxiety or depressive symptoms.…”
Section: Sleep and Attachmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Troxel et al (2007) reported that, among depressed women, those with higher levels of attachment anxiety had a lower percentage of stage 3/4 sleep and shorter sleep latencies. In anxiously attached individuals, Sloan et al (2007) reported an association between insecure attachment and the degree of α-power sleep (a form of light sleep), independent of anxiety or depressive symptoms.…”
Section: Sleep and Attachmentmentioning
confidence: 97%
“…A number of recent reports have documented statistically significant associations between measures of sleep and attachment processes in infants (McNamara, Belsky, & Fearon, 2003), children (Keller, El-Sheikh, & Buckhalt, 2008), and adults (Scharfe & Eldredge, 2001; Sloan, Maunder, Hunter, Moldofsky, 2007; Mikulincer & Shaver, 2011;Troxel, Cyranowski, Hall, Frank, & Buysse, 2007; Veredecias, Jean-Louis, Zizi, Casimir, & Browne, 2009). In adults, Verdecias et al (2009) reported that individuals characterized by a preoccupied/anxious attachment style were likely to report elevated rates of daytime napping and the use of sleep-inducing medications, independent of their demographic and subjective characteristics.…”
Section: Sleep and Attachmentmentioning
confidence: 99%
“…Such feelings of safety and security (or its absence) are likely to be particularly important for optimizing sleep quality in the context of couple relationships. In fact, several studies have shown that insecurity in close relationships (i.e., attachment anxiety)is an independent correlate of poor subjective sleep quality and decreased sleep depth (as measured by polysomnography) in both women and men (Carmichael & Reis, 2005; Hicks & Diamond, 2011; Scharfe & Eldredge, 2001; Sloan, Maunder, Hunter, & Moldofsky, 2007; Troxel et al, 2007; Verdecias, Jean-Louis, Zizi, Casimir, & Browne, 2009). However, most of the extant research on relationship quality and sleep has utilized cross-sectional designs and has not considered the potential for bidirectional associations that unfold over time.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the limited extant literature suggests that higher levels of attachment anxiety are associated with abnormalities in sleep architecture, including reductions in Stage 3 + 4 sleep in depressed women (27) and increased alpha intrusion into non-rapid eye movement (NREM) sleep in fibromyalgia patients (28), reduced sleep efficiency (29), and poorer subjective sleep quality in healthy married couples (30), college students (31), and community-dwelling senior (32). To date, however, no study has examined attachment anxiety as a correlate of sleep in the context of military veterans with PTSD symptoms, despite the fact that attachment style has been implicated in the adjustment and prognosis in PTSD populations and that sleep disturbances are a cardinal symptom of PTSD.…”
mentioning
confidence: 99%